1976
DOI: 10.1524/zpch.1976.101.1-6.255
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Förster's Theory of Long-Range Energy Transfer to Donor-Acceptor Pairs in Systems of Molecular Dimensions

Abstract: Förster's treatment of the statistics of long-range energy transfer in threedimensional systems of statistically distributed donor and acceptor molecules is extended to the two-dimensional and one-dimensional cases. The fluorescences show a different time dependence in each case. A general theory and approximate formulae for the time behaviour of the fluorescences of single donoracceptor pairs are also derived and applied to microscopic chemical or biological arrangements of different dimensionality such as sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 9 publications
4
28
0
Order By: Relevance
“…For the same diffusion coefficients longer donor decay times result in larger shifts, as expected with the additional time for D-to-A diffusion. Analytical expressions are available for RET in two dimensions without diffusion (Wolber and Hudson, 1979;Dewey and Hammes, 1986;Hauser et al, 1976;Estep and Thompson, 1979). We confirmed that the frequency responses calculated using our algorithm without diffusion (---) were equivalent to the known analytical expressions.…”
Section: Simulated Time-dependent Donor Decay With Ret and Two-dimenssupporting
confidence: 77%
See 2 more Smart Citations
“…For the same diffusion coefficients longer donor decay times result in larger shifts, as expected with the additional time for D-to-A diffusion. Analytical expressions are available for RET in two dimensions without diffusion (Wolber and Hudson, 1979;Dewey and Hammes, 1986;Hauser et al, 1976;Estep and Thompson, 1979). We confirmed that the frequency responses calculated using our algorithm without diffusion (---) were equivalent to the known analytical expressions.…”
Section: Simulated Time-dependent Donor Decay With Ret and Two-dimenssupporting
confidence: 77%
“…An alternative approach is to use resonance energy transfer (RET) to study the membranes (Fung and Streyer, 1978;Wolber and Hudson, 1979;Dewey and Hammes, 1986;Hauser et al, 1976;Estep and Thompson, 1979), which can be expected to provide information over distances comparable with the Forster distance (R 0 ), which are typically in the range of 25 to 60 Å. Such studies provide information on the spatial distribution and/or distance between donor (D) and acceptors (A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…then, upon incorporation of acceptor probe with a concentration of n i molecules/area unit, the decay becomes complex (e.g., Hauser et al, 1976),…”
Section: Introductionmentioning
confidence: 99%
“…generally useful for studies of conformational distributions of between sites on a random coil polypeptide (4)(5)(6) or between lipids in cell membranes (7)(8)(9)(10)(11)(12)(13). In such cases the steady-state data can only yield a single apparent distance or demonstrate consistency of the data with a random distribution of D-A pairs.…”
Section: Introductionmentioning
confidence: 99%